Aging-dependent changes in rat heart mitochondrial glutaredoxins—Implications for redox regulation - Xing-Huang Gao; Suparna Qanungo; Harish V. Pai; David W. Starke; Kelly M. Steller; Hisashi Fujioka; Edward J. Lesnefsky; Janos Kerner; Mariana G. Rosca; Charles L. Hoppel; John J. Mieyal (Redox Biology, 2013)
Clinical and animal studies have documented that hearts of the elderly are more susceptible to ischemia/reperfusion damage compared to young adults. Recently we found that aging-dependent increase in susceptibility of cardiomyocytes to apoptosis was attributable to decrease in cytosolic glutaredoxin 1 (Grx1) and concomitant decrease in NF-κB-mediated expression of anti-apoptotic proteins. Besides primary localization in the cytosol, Grx1 also exists in the mitochondrial intermembrane space (IMS). In contrast, Grx2 is confined to the mitochondrial matrix. Here we report that Grx1 is decreased by 50–60% in the IMS, but Grx2 is increased by 1.4–2.6 fold in the matrix of heart mitochondria from elderly rats. Determination of in situ activities of the Grx isozymes from both subsarcolemmal (SSM) and interfibrillar (IFM) mitochondria revealed that Grx1 was fully active in the IMS. However, Grx2 was mostly in an inactive form in the matrix, consistent with reversible sequestration of the active-site cysteines of two Grx2 molecules in complex with an iron–sulfur cluster. Our quantitative evaluations of the active/inactive ratio for Grx2 suggest that levels of dimeric Grx2 complex with iron–sulfur clusters are increased in SSM and IFM in the hearts of elderly rats. We found that the inactive Grx2 can be fully reactivated by sodium dithionite or exogenous superoxide production mediated by xanthine oxidase. However, treatment with rotenone, which generates intramitochondrial superoxide through inhibition of mitochondrial respiratory chain Complex I, did not lead to Grx2 activation. These findings suggest that insufficient ROS accumulates in the vicinity of dimeric Grx2 to activate it in situ.